2020
DOI: 10.1111/bjp.12495
|View full text |Cite
|
Sign up to set email alerts
|

The Supervisory Alliance in Group Supervision

Abstract: In this paper the author explores the ways in which a supervision group can be a source of ruptures in the supervisory alliance. Furthermore, the group's involvement in repair of the supervisory alliance is examined. The author draws upon empirical material from supervision sessions with a supervision group consisting of one supervisor and four novice psychotherapists conducting psychodynamic psychotherapy at a university clinic. Based on the work of W.R. Bion, the paper argues that, in group supervision, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 27 publications
0
3
0
1
Order By: Relevance
“…The authors described how these conditions can lead to "task drift" (Counselman & Weber, 2004, p. 129) characterized by discussion moving away from clinical work and toward participants' personal lives. This dynamic can lead to an overabundance of peer support and advice giving within groups (Borders, 2012;Hedegaard, 2020), and participants' qualitative and quantitative (i.e., pertaining to discussing cases) responses suggest the groups were trending toward this dynamic.…”
Section: Experiences Of Hindrancesmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors described how these conditions can lead to "task drift" (Counselman & Weber, 2004, p. 129) characterized by discussion moving away from clinical work and toward participants' personal lives. This dynamic can lead to an overabundance of peer support and advice giving within groups (Borders, 2012;Hedegaard, 2020), and participants' qualitative and quantitative (i.e., pertaining to discussing cases) responses suggest the groups were trending toward this dynamic.…”
Section: Experiences Of Hindrancesmentioning
confidence: 99%
“…Prior research also has suggested that personal and group dynamics (in this study, Personal factors and Group factors) can both contribute to and be a byproduct of this dynamic. In a study of the supervisory alliance in group supervision, Hedegaard (2020) found that passivity among group members can lead to alliance ruptures and negatively interact with (i.e., worsen) a group's tendency toward nondisclosure. Further, participants' fear of being critical and being criticized can heighten anxiety around discussing one's work with peers, especially when group members are not familiar with one another (Counselman & Weber, 2004), as was the case in the present study.…”
Section: Experiences Of Hindrancesmentioning
confidence: 99%
“…The microaggression could be considered a cultural rupture in the group supervision process; dealing with such ruptures is a critical multicultural supervision competency (Casmar, 2019). Intentional repair is crucial to preserving and strengthening the group supervisory alliance, and doing so requires directly and openly addressing the rupture (Hedegaard, 2020; Watkins, 2021; Watkins et al, 2016). We see that intentional approach applied to the group supervision process in this example: Building on a foundation of cultural humility and cultural comfort, appropriate use of the cultural opportunity allowed for the possibility of repair.…”
Section: Infusing Mco Into the Group Supervision Of Psychotherapymentioning
confidence: 99%
“…Mittlerweile wurden in der Forschung verschiedene Quellen identifiziert, die einen Bruch der Arbeitsbeziehung zwischen Supervisor/in und therapeutisch tätigem/tätiger Supervisand/in verursachen können: Eher allgemeinere Quellen, wie eine fehlende Passung zwischen Erwartungen und interpersonelle Dynamiken (Bernard und Goodyear 2019), aber auch für klinische Supervision spezifischere Quellen, wie unterschiedliche Ansichten über Patient/innen, die von den Supervisand/innen behandelt werden (Hedegaard 2016). Hedegaard (2020) zeigte in einer Untersuchung von Supervisionsgruppen, dass die Gruppe durch die mit ihr einhergehenden gruppendynamischen Prozesse ebenfalls eine wichtige Setting-spezifische Quelle für Brüche darstellt.…”
Section: Brüche In Der Beratungspraxisunclassified